Somatic mutation in acute myelogenous leukemia cells imitate novel germline HLA-A allele: a case report - Mrázek, František; Onderková, Jana; Szotkowski, Tomáš; Königova, N; Ambruzova, Z; Raida, Luděk (Tissue antigens, 2014)
A somatic mutation of the human leukocyte antigen (HLA)-A gene revealed in tumour cells of acute myelogenous leukemia (AML) is described. A patient with AML and her siblings were routinely typed for HLA in order to find a suitable donor for haematopoietic stem cell transplantation. Sequencing-based typing of the initial patient's sample characterized by high proportion of blasts revealed unknown G/A exchange at position 781 of the HLA-A gene (exon 4) associated with HLA-A*02:01 allele. Importantly, this G781A variant was completely absent in the patient's remission sample obtained after the clearance of blasts. Our results are a reminder that HLA mutations in tumour cells may interfere with routine HLA typing and should always be considered, namely, in patients with haematological malignancies.
Keywords: zárodečné mutace; dospělí; Germ-Line Mutation; Base Sequence; Female; Adult; ženské pohlaví; substituce aminokyselin; lidé; Hematopoietic Stem Cell Transplantation; Molecular Sequence Data; transplantace hematopoetických kmenových buněk; Amino Acid Substitution; Mutation, Missense; Siblings; Humans; molekulární sekvence - údaje; Remission Induction; missense mutace; Point Mutation; Neoplastic Stem Cells; Exons; indukce remise; akutní myeloidní leukemie; bodová mutace; sekvence nukleotidů; alely; sourozenci; Alleles; exony; HLA-A2 Antigen; testování histokompatibility; Histocompatibility Testing; Leukemia, Myeloid, Acute; nádorové kmenové buňky; HLA-A2 antigen